Integrating Maslow’s Hierarchy of Needs into the Strategic Management of Extracurricular Programs: A Case Study at SMP Darussalam Medan - Sibarani, Wardah Sahrani; Hadijaya, Yusuf (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study examines how SMP Darussalam Medan strategically manages extracurricular programs through planning, organization, implementation, and evaluation, analyzing them using Maslow’s Hierarchy of Needs. Using a descriptive qualitative approach, data were collected via interviews with key stakeholders, direct observations, and document analysis. The findings reveal that extracurricular management systematically addresses students’ needs—from physiological and social needs to esteem and self-actualization—by offering diverse activities, collaborative planning, and reward strategies, including tuition waivers. Unlike much previous research that focuses mainly on program outcomes, this study shows how each management stage is intentionally aligned with students’ motivational needs, helping sustain engagement and talent development over time. Key supporting factors include collaboration among teachers and coaches, parental involvement, and adequate facilities. At the same time, challenges remain in the form of budget constraints and declining participation toward the end of the semester. This study contributes to the literature by demonstrating the practical integration of Maslow’s theory in a secondary school context and recommends strengthening reward programs and building external partnerships to further enrich student experiences and maintain motivation.